Charlemagne's black stones : the re-use of Roman columns in early medieval Europe - Peacock, D. P. S.
What were the 'black stones' about which Charlemagne wrote to King Offa of Mercia just before AD 800? How do these special blocks fit into the broader pattern in re-using Roman columns in early medieval buildings?